ANALISIS KINERJA BISNIS INTERNAL PERUSAHAAN PUPUK ORGANIK CV MULIA ORGANIK TURI SLEMAN - (Sunardi dan Akimi), Sunardi Akimi (UPPM Politekik Pembangunan Pertanian Yogyakarta Magelang (Polbangtan Yoma), 2018)
The purpose of this study was to analyze the internal business performance of organicfertilizer companies, CV Mulia Organik during the 2014-2016 period. This research is acase study, the selection method uses purposive sampling. While respondents consisted ofnine employee respondents and two respondents of CV Mulia Organik customers. Datacollection methods are obtained from secondary data secondary data with documentation. This research was conducted using an internal business perspective with Supply Lead Time (SLT) and capacity calculations. The results obtained result that overall internal businessperformance of the CV Mulia Organic, it’s performance not good.Keywords: Performance, Internal Business, Organic Fertilizer.